OPTIMIZING EVACUATION ROUTES IN INDONESIAN URBAN SETTINGS WITH RESIDENTIAL AND SMALL INDUSTRIAL ZONES USING PATHFINDER SIMULATION - Hardiningtyas, Dewi; Tama, Ishardita Pambudi; Sholihah, Qomariyatus; Aprilisia, Nita (JEMIS (Journal of Engineering & Management in Industrial System), 2024)
The rapid urbanization in Indonesia has resulted in increased complexity within its urban settings, particularly in areas combining residential and small industrial zones. Effective evacuation planning is crucial to ensure the safety of inhabitants during emergencies. This study explores the optimization of evacuation routes in such mixed-use urban areas using Pathfinder simulation software. Two scenarios were examined: one with two assembly points and another with three assembly points. The simulations were conducted in a densely populated area in Malang City, Indonesia known for its combination of residential and small industrial units. The results indicate that the scenario with three assembly points significantly enhances evacuation efficiency compared to the two-assembly point scenario. Specifically, the three-assembly point configuration reduced overall evacuation times and minimized congestion at critical junctures, allowing for smoother and faster evacuation flows. The findings underscore the importance of strategically placing assembly points to improve the distribution of evacuees and reduce potential bottlenecks. This study contributes to the body of knowledge on urban evacuation planning in mixed-use settings and provides practical insights for urban planners and emergency management authorities in Indonesia. The use of advanced simulation tools like Pathfinder offers a valuable approach to optimize evacuation strategies, ensuring better preparedness and response in the face of urban emergencies.